Back Cover: 2, 4, 6‐Triarylphosphinines versus 2, 4, 6‐Triarylpyridines: An Investigation of the Differences in Reactivity between Structurally Related Aromatic Phosphorus and Nitrogen Heterocycles (Chem. Eur. J. 43/2013). Issue 43 (14th October 2013) - Weemers, Jarno J. M.; Wiecko, Jelena; Pidko, Evgeny A.; Weber, Manuela; Lutz, Martin; Müller, Christian
<x xml:space="preserve">Abstract</x> The differences in reactivity between structurally related 2, 4, 6‐triarylphosphinines and 2, 4, 6‐triarylpyridines towards IrIII and PdII have been investigated. Although phosphinines undergo facile CH activation with [Cp*IrCl2] in the presence of NaOAc, this reaction does not proceed with the corresponding pyridine derivatives. On the other hand, pyridines can be selectively ortho‐metalated with Pd(OAc)2, leading to acetate‐bridged dimeric species. The reaction of phosphinines with Pd(OAc)2 led instead to the formation of unusual cofacial oxidative coupling products, which consist of a phosphorus‐containing cage structure. For more details, see the Full Paper by C. Müller et al. on page 14458 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>